Dicrostonyx torquatus - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Dicrostonyx torquatus (Pallas 1778) [Mus] torquatus Pallas 1778, Nova Spec. Quad. Glir. Ord.: 206. Type Locality: Russia, Siberia, mouth of Ob River. Vernacular Names: Palearctic Collared Lemming. Synonyms: Dicrostonyx chionopaes G. M. Allen 1914; Dicrostonyx lenae (Kerr 1792); Dicrostonyx lenensis (Pallas 1779); Dicrostonyx pallida (Middendorff 1853); Dicrostonyx ungulatus (Von Baer 1841). Distribution: Palearctic tundra from White Sea, W Russia, to Chukotski Peninsula, NE Siberia, and Kamchatka (Nikanorov, 2000); including Novaya Zemlya and New Siberian isls, Arctic Ocean (Corbet, 1978 c Jarrell and Fredga, 1993:Fig. 5). Conservation: IUCN – Lower Risk (lc). Discussion: Once believed to encompass most or all New World populations (e.g., Rausch, 1953, 1963 b ), but karyotypic and breeding evidence (summarized by Jarrell and Fredga, 1993) supports the strict application of D. torquatus for only Eurasian populations (also see Fedorov et al., 1999 a ). Chromosomal traits of populations from the Polar Urals ( torquatus ), and those from the Laptev Sea coast, and Rautan Isl off the coast of the Chukotka Peninsula ( chionopaes ) are similar, and crosses between these two subspecies yield fertile progeny (Gileva, 1980). Unusual sex-chromosome constitution and other chromosomal information summarized by Gileva et al. (1980), Gileva (1983), and Zima and Král (1984). Phylogeographic clades identified from restriction-site analysis of mitochrondrial DNA are mostly congruent with chromosomal races (Fedorov et al., 1999 a ). Although absent from Great Britain’s modern fauna, the species occurred there during Pleistocene and Last Glacial (Late Palaeolithic) times (Sutcliffe and Kowalski, 1976; Yalden, 1999). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Cricetidae, pp. 955-1189 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 973, DOI: 10.5281/zenodo.7316535